Ion Channels and Plant Stress Responses - Demidchik, Vadim; Maathuis, Frans; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book aims to provide a range of perspectives on an area that is very topical at present in plant biology: the role of ion channels in plant stress responses. Functions of cation and anion channels in the sensing and encoding of major biotic and abiotic stimuli, stress signal transduction and metabolism adjustment are examined at the cellular and molecular levels. Particular emphases of the book are on new insights into plant Ca2+ signaling, salinity tolerance mechanisms, cyclic nucleotide gated channels and the regulation of stress reactions among oxygen-derived species.
Ion Channels and Plant Stress: Past, Present, and Future -- The Role of Ion Channels in Plant Salt Tolerance -- Cation Channels and the Uptake of Radiocaesium by Plants -- Ion Channels in Plant Development -- Potassium and Potassium-Permeable Channels in Plant Salt Tolerance -- Regulation of Ion Channels by the Calcium Signaling Network in Plant Cells -- The Role of Cyclic Nucleotide-Gated Channels in Cation Nutrition and Abiotic Stress -- The Function of Cyclic Nucleotide-Gated Channels in Biotic Stress -- New Approaches to Study the Role of Ion Channels in Stress-Induced Signalling: Measuring Calcium Permeation in Plant Cells and Organelles Using Optical and Electrophysiological Techniques -- Vacuolar Ion Channels: Roles as Signalling Mechanisms and in Plant Nutrition -- Reactive Oxygen Species, Oxidative Stress and Plant Ion Channels.
Keywords: Life sciences; Agriculture; Biochemistry; Botany; Plant diseases; Plant physiology; Life Sciences; Plant Physiology; Plant Biochemistry; Plant Sciences; Biochemistry, general; Plant Pathology; Agriculture